Hkratna ureditev in odložitev uresničevanja pravic - Trtnik, Urška (Delavci in delodajalci, 2015)
The paper gives a systematic overview of the rights in the field of parental care and family benefits which were recently affected by one of the intervention laws, or regulated by the transitional provisions of the substantive law. As a rule, the scope of rights regarding financial benefits has been reduced, either due to the lower amount of rights or the reduced number of beneficiaries. The paper further focuses on the regulation of the calculation of the benefit up- or downwards, especially in terms of the concept of minimal and average wage.
Keywords: dopust; očetovstvo; otroški dodatek; starši